DAMPAK PERCERAIAN TERHADAP PERILAKU ANAK DAN HASIL BELAJAR - Fatkhu Yasik; Dewi Anggraeni; Aulia Sahnaz (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2019)
This study aims to examine the impact of divorce: (1) knowing the existence of a divorce factor. (2) how the impact of divorce on children's behavior. (3) what is the impact of divorce on children's learning outcomes. This study uses qualitative research. The subject of this study was MI Al Khairiyah students in Duri Kosambi Cengkareng, West Jakarta who were victims of their parents' divorce. Data collection methods used in this study are interviews, data analysis includes data reduction and coding. Validation of research data uses tringgulation where researchers conduct interviews with some of the subjects to analyze their validity with other supporters. The results of this study indicate that the impact of parental divorce on children's behavior and learning outcomes can have a negative impact. Many negative effects are expressed by emotional expressions that make the child, easily sad, irritable, naughty and sometimes become quiet and inferior to his friends whose parents are not divorced. So that there is no motivation for active learning and achievement in the class because there is no support and attention of both parents for children excited in the process of learning and growth and development